(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In today‘s competitive world academic performance is of great importance. Academicachievement in school is the predictor of future career of any individual. Schools emphasize onimproving the academic performance of the students. Parents, teachers, educators and policy makersconcern about learners‘ academic achievement and try to find out ways to improve it. There are so manyfactors which influence student‘s academic achievement particularly in mathematics, as being one of theimportant school subjects. Out of these factors socio economic background and study habits are theimportant ones which needs to be analyzed and studied in detail. Since secondary stage of schooling isvery crucial period. Academic performance is very important concern for this stage and this is the stagein which students are mature enough to be guided and form habits. Therefore, the present study focuseson investigating the academic achievement in mathematics in relation to socio economic backgroundand study habits at secondary school level.